2022
DOI: 10.3389/fnins.2022.694894
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Habits, Quality of Life and Psychosocial Aspects in the Older Age: Before and During COVID-19

Abstract: AimThis study aimed to describe sleep habits, quality of life and psychosocial aspects in older people and analyze associated differences considering the time before COVID-19 pandemic and during its first wave in Portugal.MethodsOnline survey used for data collection received answers from 914 elderly (age range 65 – 90y), from April to August 2020.ResultsSymptoms of self-perception of depression, anxiety, irritability and economic problems were not prominent in the elderly, except for worries concerning uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…Enduring high pressure, guilt, and stigma increases the risk of depression [39]. Contrary to the results of the present study, the study by de Almondes et al showed that there was no difference in depression between people with COVID and noninfected people [40]. One of the reasons for this difference can be attributed to the small number of infected people (2.1%) compared to noninfected people (97.9%) in that study.…”
Section: Discussioncontrasting
confidence: 96%
“…Enduring high pressure, guilt, and stigma increases the risk of depression [39]. Contrary to the results of the present study, the study by de Almondes et al showed that there was no difference in depression between people with COVID and noninfected people [40]. One of the reasons for this difference can be attributed to the small number of infected people (2.1%) compared to noninfected people (97.9%) in that study.…”
Section: Discussioncontrasting
confidence: 96%
“…Amicucci et al 26 believed that the elderly in Italy were less affected by COVIDRI than adolescents due to their habitual shorter sleep duration, lower sleep efficiency and more use of sleep medications prior to the pandemic. De Almondes et al 27 conducted a survey of 914 elderly people during the first outbreak wave in Portugal and found that there was no difference in sleep duration before and during the pandemic, but some aspects related to sleep, such as sleep quality, sleep efficiency, wake-up quality, sleep latency and nocturnal awakening, were worsened. These incidences were higher in older women 28 …”
Section: Vulnerable Populations With Covidrimentioning
confidence: 99%
“…Though the identified health behavior changes were small, these findings are largely consistent with our hypotheses and the previous literature. For example, Almondes et al (2022) demonstrated that older adults maintained consistent sleep schedules before and during the pandemic; however, they reported slight negative changes in sleep latency, quality, awakenings, and efficiency. Significant stress, anxiety, and depression are all factors that have been associated with poorer sleep quality for individuals during lockdown periods (Franceschini et al, 2020;Xiao et al, 2020).…”
Section: Health Behaviorsmentioning
confidence: 99%
“…For example, older adults reported increases in alcohol consumption and decreases in physical activity/increases in sedentary behaviors during the pandemic (Constant et al, 2020;Emerson, 2020;Malta et al, 2020;Suzuki et al, 2020;Niedzwiedz et al, 2021); however, some studies suggest that the magnitude of these negative health behavior changes during the pandemic is smaller for older adults compared to younger adults (Constant et al, 2020;Ferrante et al, 2020;Giustino et al, 2020;Malta et al, 2020;Rogers et al, 2020;Niedzwiedz et al, 2021). Similarly, Almondes et al (2022) demonstrated negative changes in older adults' reported sleep quality, whereas Pinto et al (2020) suggested that older adults are less likely to complain about sleep difficulties during the early months of the pandemic. Furthermore, older adults in China reported engaging in adaptive health behaviors in response to the pandemic like eating a balanced diet, limiting alcohol, and maintaining adequate sleep schedules (Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%